2012
DOI: 10.1111/j.1528-1167.2012.03424.x
|View full text |Cite
|
Sign up to set email alerts
|

Focal and generalized EEG paroxysms in childhood absence epilepsy: Topographic associations and distinctive behaviors during the first cycle of non‐REM sleep

Abstract: SUMMARYPurpose: To better understand the nature of the focal spike-wave discharges (FSWDs) and focally led generalized spike-wave discharges (GSWDs) in typical childhood absence epilepsy (CAE) and by implication their nosologic and taxonomic significance. Methods: Twenty-four abnormal video-electroencephalography (EEG) studies from 13 consecutive children with CAE and good response to appropriate antiepileptic drugs (AEDs) were analyzed. We studied the association between the topography of absence onset and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 70 publications
1
31
0
2
Order By: Relevance
“…These observations demonstrate the involvement of the hippocampus and the interplay between the hippocampal and cortico-thalamocortical circuits in typical absence seizures [34,35]. Some clinical studies have also reported temporal lobe involvement in typical absence seizures [31,32]. Focal spike slow-wave discharges observed in the temporal lobe in CAE patients [31], which suggests that the temporal area may be a part of the epileptic network in CAE.…”
Section: Initial-response Group (N = 12)mentioning
confidence: 92%
See 2 more Smart Citations
“…These observations demonstrate the involvement of the hippocampus and the interplay between the hippocampal and cortico-thalamocortical circuits in typical absence seizures [34,35]. Some clinical studies have also reported temporal lobe involvement in typical absence seizures [31,32]. Focal spike slow-wave discharges observed in the temporal lobe in CAE patients [31], which suggests that the temporal area may be a part of the epileptic network in CAE.…”
Section: Initial-response Group (N = 12)mentioning
confidence: 92%
“…Some clinical studies have also reported temporal lobe involvement in typical absence seizures [31,32]. Focal spike slow-wave discharges observed in the temporal lobe in CAE patients [31], which suggests that the temporal area may be a part of the epileptic network in CAE. Focal temporal electroclinical transformation from typical absence seizures was observed in video-EEG monitoring of two CAE patients [32].…”
Section: Initial-response Group (N = 12)mentioning
confidence: 96%
See 1 more Smart Citation
“…100 Psychogenic nonepileptic events (pseudoseizures) may arise during periods when the patients seem to be sleeping but the EEG showed them awake (a condition called pseudosleep). [101][102][103] Injuries and incontinence do not distinguish between epilepsy and pseudoseizures. 104 Although longer-lasting, NFLE seizures can lead to episodic nocturnal wandering but more often are temporal lobe in origin.…”
Section: Less Common Clinical Presentations Of Epileptic and Nonepilementioning
confidence: 99%
“…In a further study of childhood absence epilepsy [108] focal SWDs occurred mainly during non-CAP and CAP-B periods (periods of reduced vigilance) of NREM sleep, whereas generalized SWDs occurred during the CAP-A of NREM sleep and especially at the transition from reduced to enhanced vigilance of NREM sleep. Regarding the efforts to understand the relationship between spindles and epilepsy, these studies emphasize the importance of (a) mutual interaction between the two, (b) recognizing that different types of epilepsy may have different mechanisms and (c) the importance of observing the "bigger picture" in both time (i.e.…”
Section: Spindles and Epilepsymentioning
confidence: 99%